O mecanismo hipotensor do ácido α-lipóico em modelos de hipertensão arterial dependentes de angiotensina II envolve a inibição da ADAM17 - Queiroz, Thyago Moreira de (2014)
Oxidative stress has been indicated as a central mechanism in Ang II-dependent hypertension. Furthermore, previous studies reported that oxidative stress is associated with the impairment of angiotensin converting enzyme 2 (ACE2) compensatory activity by the disintegrin and metalloprotease 17 (ADAM17) during hypertension. In this context, -lipoic acid (LA), a potent antioxidant, has been studied by its effects on cardiovascular system, however its effects on Ang II/ROS/ADAM17/ACE2 pathway have not been studied yet. Here we used two Ang II-dependent hypertensive models, the two-kidney-one-clip (2K1C) and deoxycorticosterone-sal (DOCA-salt) hypertension. Firstly, we analyzed the effects induced by chronic treatment with LA on blood pressure, heart rate and baroreflex sensitivity (sympathetic and parasympathetic components) in renovascular hypertensive rats. Male Wistar rats underwent 2K1C or sham surgery and were maintained untouched for four weeks to develop hypertension. Four weeks post-surgery, rats were orally treated with LA (60 mg/kg) or saline for 14 days. On the 15th day, mean arterial pressure (MAP) and heart rate (HR) were recorded. In addition, baroreflex sensitivity test using phenylephrine (8 μg/kg, i.v.) and sodium nitroprusside (25 μg/kg, i.v.) was performed. Chronic treatment with LA decreased blood pressure in hypertensive animals compared to 2K1C + saline group (133.5 ± 9.3 vs 176.5 ± 9.6 mmHg, p<0.05, respectively); however, no significant changes in baseline HR were observed. Regarding baroreflex, LA treatment increased the sensitivity of both the sympathetic and parasympathetic components (−2.80 ± 0.6 vs −2.61 ± 0.4 and −4.14 ± 0.6 vs. −3.85 ± 0.5 bpm.mm Hg−1, p < 0.05, n = 8, respectively). To investigate the relationship between ADAM17 and oxidative stress, Neuro2A cells were treated with Ang-II (100 nM) 24 h after vehicle or LA (500 μM). ADAM17 expression was increased by Ang-II (100.2 ± 0.8 vs 120.5 ± 9.1%, p<0.05) and decreased after LA (120.5 ± 9.1 vs 69.0 ± 0.3%, p<0.05). In other set of experiments, LA reduced ADAM17 (92.9 ± 5.3 vs control: 77.3 ± 3.3%, p<0.05) following its overexpression. Moreover, ADAM17 activity was reduced by LA in ADAM17-overexpressing cells (109.5 ± 19.8 vs 158.0 ± 20.0 FU/min/μg protein, p<0.05), in which ADAM17 overexpression increased oxidative stress (114.1 ± 2.5 vs 101.0 ± 1.0%, p<0.05). Conversely, LA-treated cells attenuated ADAM17 overexpression-induced oxidative stress (76.0 ± 9.1 vs 114.1 ± 2.5%, p<0.05). In DOCA-salt-hypertensive mice, a model in which ADAM17 expression and activity are increased, hypertension was blunted by pretreatment with LA (119.0 ± 2.4 vs 131.4 ± 2.2 mmHg, p<0.05). In addition, LA improved dysautonomia and baroreflex sensitivity. Furthermore, LA blunted the increase in the expression of NADPH oxidase subunits as well as the increase in ADAM17 and decrease in ACE2 activities in the hypothalamus of DOCA-salt hypertensive mice. Our data suggest that chronic treatment with LA promotes antihypertensive effect and improves baroreflex sensitivity and autonomic function in rats with renovascular hypertension as well as in DOCA-salt mice. Therefore, these data suggest that LA might preserve ACE2 compensatory activity by breaking the feed-forward cycle between ADAM17 and oxidative stress, resulting in reduction in hypertension.